DAMPAK PAJAK KARBON TERHADAP KELANGSUNGAN BISNIS - Alikhan Salim; Mahfud Sidiq (REMITTANCE: JURNAL AKUNTANSI KEUANGAN DAN PERBANKAN, 2022)
A Carbon Dioxide Tax is a tax imposed on the use of carbon-based fuels. Its application in Indonesia is based on UU No. 7/2021 on the Harmonization of Tax Regulations and Presidential Regulation No. 98/2021 on the Implementation of the NEK. Using the literature study research method to find and analyze the implementation of the carbon tax in Indonesia. The results of the study show that the impact of the carbon tax on business includes the relocation of aluminum, steel, and nickel smelters to other countries that have not implemented a carbon tax, and the increased price due to the carbon tax makes business actors substitute minerals that produce high carbon with low ones. and the use of renewable energy in the mining sector will increase